1982
DOI: 10.1128/aem.43.1.97-103.1982
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diluents, media, and membrane filters on detection fo injured waterborne coliform bacteria

Abstract: Pure cultures of Escherichia coli, Klebsiella pneumoniae, Enterobacter aerogenes, and Citrobacter freundii were injured (>90%) in water from a dead-end section of the Bozeman, Montana, distribution system. The effects of the following laboratory variables on the enumeration efficiency of injured and undamaged control cells were examined: (i) diluent composition, temperature, and time of exposure; (ii) media, using various formulations employed in enumerating gram-negative bacteria; and (iii) surface pore morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 45 publications
1
62
1
1
Order By: Relevance
“…Cell injury due to impaction effect has been reported in other spheres of microbiology such as membrane filtration (McFeters et al 1982) and bioaerosol collection on agar surface (Stewart et al 1995;Terzieva et al 1996). Our literature scan did not indicate such documentations with respect to spread plating except for our recent report .…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Cell injury due to impaction effect has been reported in other spheres of microbiology such as membrane filtration (McFeters et al 1982) and bioaerosol collection on agar surface (Stewart et al 1995;Terzieva et al 1996). Our literature scan did not indicate such documentations with respect to spread plating except for our recent report .…”
Section: Discussioncontrasting
confidence: 51%
“…The situation on agar surface could be different in that the cells get embedded inside agar, thus minimizing the adverse effects due to impaction. There is also a possibility of recovery of some of the injured cells on nutrient agar surface (McFeters et al 1982;Terzieva et al 1996), which may explain the null effect in some of the organisms.…”
Section: Discussionmentioning
confidence: 99%
“…These results disagree with those of other studies (Saleh 1980 8 ;Volterra et al 1985), which suggested that the MF technique was more ef®cient (gave higher numbers) for faecal streptococci counts than the MPN procedure. Previous studies have also reported a lower sensitivity of the MF technique in recovering coliforms when compared with the MPN procedure (Shipe and Cameron 1954;McFeters et al 1982;Jacobs et al 1986); on the other hand, Dutka and Tobin (1976), Janardan et al (1977) and Massa et al (1989) found that the MF technique was more ef®cient (gave higher numbers) for coliform counts than the MPN procedure. There are several possible explanations for these discrepancies, the foremost being the different principles on which the two techniques are based, i.e.…”
Section: Resultsmentioning
confidence: 94%
“…Filters commonly utilized for collection include cellulosebased, nylon, and glass fibers with pore sizes down to 0.02 m (for viral analysis) (78). The drawbacks of filtration include desiccation of the microorganisms on the filter surface due to filtration rate and time (higher flow rates and longer filtration times), the preferential concentration of spore-forming microbes over other community members as non-spore formers are desiccated during rapid or long filtration times (culturebased studies), filter size (37 mm versus 47 mm; i.e., larger diameters limit stacking of cells in a high particle load environment), and filter type (a thicker filter can wick nutrients to cells, thereby limiting close-contact nutrient shock of stressed cells) (27,83,111,150,231).…”
Section: Collectionmentioning
confidence: 99%